Modulating Factors of Resilience in Patients Diagnosed with Breast Cancer - Lizandra García Monzón; Víctor René Navarro Machado (Revista Finlay)
Introduction: resilience modulating factors serve as health protecting agents and can influence in facing the disease of patients with cancer. Objective: to specify the distinctive features of modulating resilience factors according to: optimism, emotional intelligence and social support in patients diagnosed with breast cancer. Methods: descriptive, prospective study, of a case series, in the municipality of Rodas from 2014 to 2015. It included all patients diagnosed with breast cancer, with one, three and five years of survival. The applied instruments were: general data questionnaire, emotional intelligence test, optimism and social support questionnaires. The variables analyzed were: age, level of schooling, marital status, occupation, presence of optimism, degree of emotional intelligence, support need. An in-depth study was carried out and the questionnaires of general data, optimism, social support and emotional intelligence examination were applied. Measures of central tendency, dispersion measures and percentage were used as a summary measure for qualitative variables. Results: 37 mainly married, housewives, were studied, senior high schooling and aged 59.5 years average. From the resilience modulators, optimism was present in patients with 3 and 5 years of evolution, an average degree of emotional intelligence predominated in most patients and they perceive that they need between almost nothing and something of social support. Conclusion: there was homogeneity in the socio-demographic and clinical aspects of the patients. Optimism was less present at the beginning of the disease, but later it was related to the evolution in years. Needs of social and emotional support increased with the time of evolution of this condition.